Penerapan Sistem Pendukung Keputusan Menentukan Ranking Sekolah Unggulan Kabupaten Nias Dengan Menggunakan Metode AHP - Kristiani Zega; Hasanul Fahmi (Program Studi Teknik Komputer, Fakultas Teknik. Universitas Serambi Mekkah, 2021)
One of the computational methods that is currently developing is the Decision Support System method. Decision Support System is part of a computer-based information system including a knowledge-based system that is used to support decision making. In choosing a school, prospective students tend to follow their friends without knowing which school to go to in accordance with educational standards. The Analytical Hierarchy Process (AHP) method was declared feasible because it is faster and more effective, so it can be ascertained that the application of the AHP method can solve problems in the selection of superior schools in Nias Regency. Alternative data consisted of SMAN 1 Gido, SMAN 1 Botomuzoi, SMAN 2 Gunung Sitoli, SMAN 1 Gunungsitoli. Data criteria include Teacher Education, Building Conditions, School Cleanliness, Facilities. Processing of SPK using the AHP method resulted in the school of SMAN 2 Gunung Sitoli having the highest score of 2.68. Web-based system built using PHP with AHP decision support methods and MySQL database.